Increased Content of Resistin in Epicardial Adipose Tissue of Patients with Advanced Coronary Atherosclerosis and History of Myocardial Infarction - Rachwalik, Maciej; Zyśko, Dorota; Diakowska, Dorota; Kustrzycki, Wojciech (The Thoracic and Cardiovascular Surgeon, 2014)
Objectives The aim of the study was to assess whether the plasma level and content of adipokines, in adipose tissue, is associated with a medical history of myocardial infarction.Patients and Methods The study group consisted of 33 consecutive patients (12 females, 21 males, aged 68.6 ± 6.8 years) who underwent cardiac bypass surgery. Patients were divided into groups; group 1 presented with a history of myocardial infarction and group 2 presented without a history of myocardial infarction. During cardiac surgery, samples of epicardial adipose tissue, adipose tissue located at internal mammary artery, subcutaneous adipose tissue, and blood samples were taken for further assessment.Significantly higher levels of resistin in adipose tissue from the epicardial tissue were found in group 1 than in group 2: median and interquartile range, respectively, 37.2 (8.9–121.5) ng/g versus 15.0 (7.1–24.1) ng/g; p < 0.049. Multivariate analysis found that previous myocardial infarction was associated with male gender, older age, and higher content of resistin in epicardial adipose tissue.Conclusion The resistin content in epicardial adipose tissue in patients with advanced coronary atherosclerosis seems higher in those with a history myocardial infarction. Increased resistin epicardial content seems related to the previous myocardial infarction independent of the other established risk factors such as age and male gender. The importance of paracrine function of adipose pericardial tissue in the occurrence of complications of atherosclerosis merits further investigations.
Keywords: coronary artery disease; adipokines; coronary artery bypass graft; epicardial adipose tissue